Kepemimpinan Berbasis Pancasila dalam Mengelola Konflik dan Membangun Kolaborasi Guru di SMK Maharati - Dianto, Aris; Sulton, Sulton (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
This research is motivated by the complexity of intergenerational teacher conflicts that often hinder synergy in the Vocational High School (SMK) environment. This study specifically examines the implementation of Pancasila values in conflict resolution strategies and collaborative team building by school principals. Using a qualitative case study approach at SMK Maharati, data was collected through in-depth interviews, participant observation, and document studies. The research findings reveal that conflicts originating from differences in educational paradigms, digital divides, and cultural diversity were successfully transformed through a leadership approach that operationalizes the principles of Pancasila. The principal acted as a facilitator who applied deliberation for consensus (fourth principle) in mediation, social justice (fifth principle) through reverse technology mentoring programs, and strengthened unity (third principle) and Bhinneka Tunggal Ika through cross-group collaboration designs. This study concludes that educational leadership characterized by Pancasila is not only effective in resolving conflicts integratively but also capable of building a sustainable collaborative culture that converts diversity into a source of collective strength. The practical implication is that this leadership model can be adopted as a framework for developing principal capacity in diverse societal contexts to create harmonious and productive educational ecosystems.